THE EFFECT OF REVENUE SHARING FUNDS, GENERAL ALLOCATION FUNDS, SPECIAL ALLOCATION FUNDS AND SPECIAL AUTONOMY FUNDS ON CAPITAL EXPENDITURE WITH ECONOMIC GROWTH AS MODERATING VARIABLES IN THE GOVERNMENT OF THE DISTRICT / CITY IN ACEH PROVINCE IN 2008 – 2017 - Ananda, Rana Fathihah (Asosiasi Dosen Akuntansi Indonesia, 2019)
This study aims to determine and analyze whether Revenue Sharing Funds, General Allocation Funds, Special Allocation Funds and Special Autonomy Funds have a simultaneous and partial effect on Capital Expenditure in district / city governments in Aceh Province and to find out and analyse whether the variable Economic Growth as a variable moderating can strengthen and weaken the influence of Revenue Sharing Funds, General Allocation Funds, Special Allocation Funds and Special Autonomy Funds on Capital Expenditures in district / city governments in Aceh Province. The results of the study simultaneously show the Revenue Sharing Fund, General Allocation Fund, Special Allocation Fund and Special Autonomy Fund significantly affect Capital Expenditures. Partially, Revenue Sharing Funds does not have a significant effect on capital expenditure; General Allocation Funds have a significant effect on capital expenditure; Special Allocation Funds have no significant effect on capital expenditure; The Special Autonomy Fund has a significant effect on capital expenditure. Economic Growth Variable as a moderator is unable to moderate the effect of Revenue Sharing, General Allocation Funds, Special Allocation Funds and Special Autonomy Funds on Capital Expenditures.